The Business Review: An analysis of section 417 of the Companies Act 2006 - Keay, Andrew (The Enlightened Shareholder Value Principle and Corporate Governance, 2013)
I indicated in the last chapter that there are two legislative limbs (or pillars) to enlightened shareholder value (ESV). The first, contained in s.172 of the Companies Act 2006 ('the Act') was the subject of Chapter 4. As we saw in the last chapter, s.172 lays down the duty of the directors. This chapter now examines the second limb, found in s.417 of the Act. This provision is complementary to s.172 and addresses the need for companies to report on, inter alia, how the directors have addressed their duty under s.172. It is, therefore, an accountability mechanism as far as the actions of the directors are concerned.